DYNAMICS OF DISABILITY ADJUSTED LIFE YEARS (DALY) AS A RESULT OF PREMATURE MORTALITY OF CHILDREN AT THE AGE OF 0–17 YEARS IN TOMSK REGION IN 2008–2012 - О. S. Kobyakova; I. A. Deev; N. Ya. Nesvetailo; V. А. Boykov; I. P. Shibalkov; E. S. Kulikov; M. N. Milkevitch; E. А. Starovoitova (Вопросы современной педиатрии, 2014)
The DALY indicator (Disability Adjusted Life Years) is widely used for the assessment of a contribution of various diseases to losses of the population health and of the analysis of activity efficiency of health care systems. Background: Research objective was to evaluate dynamics of the DALY indicator as a result of premature mortality of the child population of Tomsk region during 2008-2012. Patients and methods: DALY calculation as a result of premature mortality of the child population of the region during the period from 2008 to 2012 is made. While calculating the data of Territorial body of Federal service of state statistics for the Tomsk Region (Rosstat) which included a sex of the dead, day, month and year of death, place of residence, cause of death, day, month and year of birth of the dead was used. The number and gender and age structure of the population of the Tomsk Region according to Rosstat data were also considered. Results: The DALY decrease by 16,5% in child population at the age of 0–17 years is observed in the Tomsk region during the period from 2008 to 2012. Following the results of 2012, DALY in studied population made 833.1 (82.3 ± 5.4) years for 10 thousand of corresponding population that is 1,1 times lower than totally in the Russian Federation, and 3.4 times lower than the universal indicator of 2010. Conclusion: The received result reflects the activity of health care system of the region, directed on integration of synthesis of theoretical and practical knowledge. Decrease in DALY among the child population in the territory of the region is promoted by a number of factors: continuous quality improvement of the medical care rendered to children, target programs on motherhood and childhood health protection realized in the territory of the region, and also functioning of the federal scientific and educational institutions promoting introduction of modern techniques of medical care delivery in practical health care.Key words: demography, DALY, health assessment of the child population.